Growth of Incumbent Firms and Entrepreneurship in Vietnam - Enrico Santarelli; Hien Thu Tran (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
This paper analyzes the relationship between the performance of incumbent firms and the net entry of new firms by combining different theoretical views of entrepreneurship. It shows that new knowledge and ideas created but not commercialized by incumbents are an important source of entrepreneurial opportunities for nascent firms. Different regression models to treat dynamics and endogeneity issues are applied to test the research hypothesis that growth of incumbent firms in a region will stimulate start-up activities by creating new profit opportunities for potential entrepreneurs. Vietnam's regional micro-data from 2000 to 2008 are used for this test. Four controlling indicators – entrepreneurial demand, market structure, regional economic environment, and market innovativeness – are found to exert a statistically significant effect on new entries.
Keywords: L25; L26; O53; R12; 330